Attitudes towards intimate partner violence against women in Latin America - Marisa Bucheli; Máximo Rossi (Global Labor Organization (GLO), 2017)
In this paper we analyze the factors that explain attitudes towards intimate partner violence against women (IPVAW) in 23 countries in Latin America and the Caribbean (LAC). Analyses of IPVAW in LAC are relatively scarce although there is growing concern about this problem in the region. We aim to assess the effect of individual and country characteristics using data from common sources for all countries. This work contributes to the sparse literature dealing with methods that attempt to assess the effect of macro variables. We perform a two-step procedure. We first estimate a logit model at the individual level, we calculate a measure of relative approval of IPVAW at country level and we use this measure as a dependent variable to estimate the effect of macro variables. Our study finds that most LAC patterns at individual level are similar to the international ones: approval of IPVAW is higher among women, people in rural areas, people in a disadvantaged socio-economic situation and individuals with some particular cultural characteristics. Unlikely international evidence, attitudes do not differ between ages. Our findings at country level show that approval of IPVAW increases with poverty, fertility rate and equal gender outcomes. It decreases with internet access and, with a lesser degree of robustness, with the time elapsed since the enactment of women's suffrage. The most novel contribution of our work is the study of the variables at country level.
Keywords: J12; J19; D03; D19; 330; intimate partner violence; attitudes; Latin America; gender roles; violence